Horizontal Accuracy Assessment of Rectified Map, Case Study: Map of Boundary Areas of Konak Forest at Rejang Lebong Regency, Bengkulu Province - Citra Dewi; Rahma Anisa; Romi Fadly; Sri Rezki Artini (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2022)
Spatial archives in the form of analog maps still encountered in several work units, however, as times progressed, the quality of these maps decreased in terms of the materials used which could affect their accuracy. There are several techniques used in converting from analog to digital maps, including scanning technique, and a unification coordinate system with the rectification method. This study aimed to find out the horizontal accuracy and the accuracy class of rectified maps. The data used was an analog map of a map of the boundary demarcation of the Konak Forest area, Rejang Lebong Regency scale 1:1000. The analog map was produced more than 30 years ago. The steps carried out in this study were preparing data from scanning analog maps, setting coordinate systems, input GCP, control rectification, calculating RMSE and CE values, analyzing, digitizing, layout. The result of the rectification map shows the use of 4GCP produces the best value with RMSE 0.14m and CE90 0,20 and the horizontal accuracy is class 1 on a scale of 1:1000. 6GCP produces RMSE 0.5m and CE90 0.75 and the horizontal accuracy is class 3 on a scale of 1:2500. 10GCP produces RMSE 0.6m and CE90 0.95 and the horizontal accuracy is class 3 on a scale of 1:2500.